Chapter The EU Research Project PLANET - Schröder, Andrea (InTechOpen, 2018)
Renewable energy sources offer unprecedented opportunities to reduce greenhouse gas emissions. But some challenges remain to be solved before their full benefits can be reaped. The main one relates to the intermittency of their electricity supply which can lead to grid problems such as congestion and imbalance between generation and demand. Energy conversion and storage has been touted as a very promising solution to all aforementioned issues. PLANET will develop a holistic decision support system for the optimal orchestration of the different energy networks for aggregators and balance responsible parties, policy makers and network operators. It will aid them to leverage innovative energy conversion in alternative carriers and storage technologies in order to explore, identify, evaluate and quantitatively assess optimal grid planning and management strategies for future energy scenarios targetting full energy system decarbonization. Moreover, an analysis of the possible synergies between electricity, gas and heat networks will be carried out by creating simulation models for the integration between energy networks and conversion/storage technologies, for example power-to-gas, power-to-heat and virtual thermal energy storage. Application of the developed tools in two different test cases in Italy and France will showcase their benefits and reveal potential grid stability issues and effective countermeasures.